Agency Conflicts And Their Relationships To Firms Performance In Jordan - Alkhazaleh, Qutaiba Khaled Abdu (2024)
There are four main objectives of this study. First, to examine the direct relationship between earnings quality, corporate governance and firm performance. Second, to examine the relationship between earnings quality, corporate governance, and investment efficiency. Third, to examine the relationship between investment efficiency and firm performance. Fourth, to examine the indirect relationship between earnings quality, corporate governance and firm performance; with investment efficiency as a mediator.